Magmatic crystallization drives zircon Zr isotopic variations in a large granite batholith. (1st February 2023) - Zhu, Zhaoxian; Zhang, Wen; Wang, Jionghui; Wang, Zaicong; Guo, Jing-Liang; Elis Hoffmann, J.; Feng, Lanping; Luo, Tao; Hu, Zhaochu; Liu, Yongsheng; Moynier, Frédéric
Abstract: Stable zirconium (Zr) isotope of magmatic zircons is a promising new tracer to understand magma differentiation in the continental crust. However, magmatic processes controlling zircon Zr isotopic variations remain poorly constrained. Here we present high-spatial-resolution in-situ methods on magmatic zircons for U-Pb age, trace elements, Hf isotopes, and stable Zr isotopes (δ 94/90 Zr relative to IPGP-Zr) as well as bulk rock δ 94/90 Zr for a large granite batholith (SiO2 = ∼73 wt%) in the Jiaodong Peninsula, eastern North China Craton. Magmatic zircons are classified into high-luminance Type-I and low-luminance Type-II zircons in the cathodoluminescence images. Both types show indistinguishable U-Pb ages and initial Hf isotopic compositions, indicating their same magma source. Yet, they differ in chemical compositions and δ 94/90 Zr values. Type-I zircons display lower δ 94/90 Zr values (−0.35‰ to 0.15‰) than Type-II zircons (0.16–0.54‰). The δ 94/90 Zr values overall increase with decreasing Zr/Hf, Th/U ratios, Ti-in-zircon temperature, and increasing U abundances in zircons, implying that zircon δ 94/90 Zr values becomes heavier with the enhanced magma differentiation. Such concomitant correlations resulted from closed-system magma crystallization without noticeable segregation of feldspar and zircon, as revealed by high Sr and Ba content, limited Eu anomalies, and mantle-like δ 94/90 Zr in the bulk rocks (−0.01 ± 0.07‰ and 0.02 ± 0.04‰). Thus, Type-I zircons incorporating light Zr isotopes crystallized at an early stage of magma solidification, while Type-II zircons grew from more evolved residual melts with elevated δ 94/90 Zr values. Zoned zircon grains with Type-I cores and Type-II rims record the prolonged crystallization history covering both stages with contrasting melt compositions; whereas oscillation zircon grains of Type-I or Type-II, crystallizing at the stable melt composition, display the restricted intragrain variations of δ 94/90 Zr, Zr/Hf, and Th/U ratios. These results demonstrate that closed-system magmatic crystallization plays a critical role in zircon Zr isotopic variations. We further propose that the variability of δ 94/90 Zr values and multiple types of Zr isotopic profiles in zircons are predominantly driven by the compositional effect of adjacent melts from which zircons crystallize. The composition-related δ 94/90 Zr variations provide a fundamental framework for understanding Zr isotopic evolution in the silicic igneous system and can be used for exploring open-system magmatic processes in the mushy pluton bodies, which are important for continental crust evolution.